2000
DOI: 10.1046/j.1365-3180.2000.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crop management practices on Echinochloa crus‐galli and Chenopodium album seed production in a maize/soyabean rotation

Abstract: Seed production of residual weed populations needs to be taken into account when estimating the long-term impact of low-input agronomic practices. The objective of this study was to measure the eects and interactions of crop, weed control, tillage practice and nutrient source on the seed production of the dominant residual weed species in a maize/soyabean rotation at two sites: Echinochloa crus-galli (L.) Beauv. on a Sainte-Rosalie clay and Chenopodium album L. on a Duravin clay loam. Seed production per unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…(), which showed greater weed densities in CA compared to conventional tillage (CONV). Conversely, several studies found that tillage did not have any effect on weed density (Perron & Légère, ; Bullied et al ., ; Shrestha et al ., ; Mandumbu et al ., ).…”
Section: Introductionmentioning
confidence: 96%
“…(), which showed greater weed densities in CA compared to conventional tillage (CONV). Conversely, several studies found that tillage did not have any effect on weed density (Perron & Légère, ; Bullied et al ., ; Shrestha et al ., ; Mandumbu et al ., ).…”
Section: Introductionmentioning
confidence: 96%
“…In the long term, effective weed control under minimum tillage could result in the depletion of the seedbank near the soil surface. Lower weed densities could be expected in the years following the adoption of conservation tillage practices (Froud-Williams et al 1984;Ball 1992), provided that residual weed populations would be prevented from producing seeds and replenishing the seedbank (Perron and Légère 2000).…”
Section: Discussionmentioning
confidence: 99%
“…for corn and soybean under mechanical versus chemical weed control in Quebec; however, the efficacy of mechanical weed control could have been improved if the timing was earlier (Perron and Légère 2000). Wide row spacing can be used in crops that are traditionally solid-seeded to facilitate inter-row cultivation (e.g., pea) (Johnson and Frick 2002).…”
Section: Substitution Of Direct Non-chemical Weed Control For Herbicimentioning
confidence: 99%
“…Increased seeding rate and seeding depth can compensate for crop damage incurred during mechanical weed control operations (Kirkland 1995;Johnson 2002a). Timing of weed control is critical to achieve optimum results (Perron and Légère 2000;Swanton et al 2002;Porter et al 2003), and may be assisted by modelling weed emergence (Forcella et al 1993;Bullied et al 2003;Grundy 2003). Mechanical weed control can also be facilitated by staggered planting of crops on a single farm so that the need to cultivate large areas at one time is avoided (Jordan 1996).…”
Section: Substitution Of Direct Non-chemical Weed Control For Herbicimentioning
confidence: 99%